2021
DOI: 10.1002/adbi.202100775
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics‐On‐a‐Chip: In Vitro Microphysiological Models for Emulating of Drugs ADME

Abstract: pharmacodynamics (PD), and toxicity studies, of the past century and continue to provide a wealth of knowledge and understanding of various diseases mechanism and therapy. [1][2][3] However, the use of these models in research and industrial applications has been a subject of heated debate, particularly, due to ethical matters and the increasing pressure by the animalright activists. [4] In addition, the phylogenetic difference between laboratory animals and humans may lead to drug failure during human clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 223 publications
(309 reference statements)
0
11
0
Order By: Relevance
“…These secretions occur under membrane transporters and require cellular barrier integrity. 26 The TEER of the RHR injury-on-chip model was evaluated as an indicator of cell−cell tight junction formation for examining the influence of RHR injury on the RPTEC monolayer. The TEER was monitored every hour from day 0 until the termination of the experiment using an in-house TEER monitoring system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These secretions occur under membrane transporters and require cellular barrier integrity. 26 The TEER of the RHR injury-on-chip model was evaluated as an indicator of cell−cell tight junction formation for examining the influence of RHR injury on the RPTEC monolayer. The TEER was monitored every hour from day 0 until the termination of the experiment using an in-house TEER monitoring system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Proximal tubular cells are the primary drivers of the active tubular secretions that are vital for drug secretion and release and metabolic excretion. These secretions occur under membrane transporters and require cellular barrier integrity . The TEER of the RHR injury-on-chip model was evaluated as an indicator of cell–cell tight junction formation for examining the influence of RHR injury on the RPTEC monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…Such metabolic biotransformations were investigated regarding the GH secretagogues (GHS) capromorelin, macimorelin, and tabimorelin (Figure 1, 1 – 3 ) by Lange et al, 135 using in‐vitro and animal in‐vivo approaches. A series of metabolites was detected for each drug; however, only a rather small intersecting set was observed when considering all products found in the in vivo (rat plasma, rat urine) and in vitro (human serum, human liver microsomes) experiments, underlining the importance of studying the metabolic fate of drugs as comprehensively and close to human physiology as possible 136 . The intact drugs of capromorelin and tabimorelin were tentatively suggested as the most suitable target analytes due to their traceability in rat urine up to 36 h following a single oral dose (0.5–1 mg) of the drug.…”
Section: Peptide Hormones Growth Factors Related Substances and Mimeticsmentioning
confidence: 99%
“…The development of a toxicology platform that realistically reproduces these interactions is urgently needed to further reveal the potential risk of MP-related blood issues. 1,3,15…”
Section: Introductionmentioning
confidence: 99%
“…The development of a toxicology platform that realistically reproduces these interactions is urgently needed to further reveal the potential risk of MP-related blood issues. 1,3,15 At present, a series of studies based on cellular experiments and mouse models has been reported for the effects of MPs on the coagulation cascade system and the toxicology of cells, etc. [16][17][18][19][20][21][22][23][24][25] However, there is still a gap in the study of the effects of MPs on the highly interacting vascular system.…”
Section: Introductionmentioning
confidence: 99%